Identification by internal affairs bodies of the causes of offenses in domestic violence in Kazakhstan - Yessentemirova, A.M.; Surkova, S.S. (Bulletin of the Karaganda University “Law Series”, 2023)
This work is devoted to the study of the main points on the identification by law enforcement agencies of the causes of offenses in domestic violence, which in the future can become preventive measures in the field of family and domestic relations. The main purpose of the study is to develop basic proposals for the further work of law enforcement agencies in identifying and reducing domestic violence in families. The study showed the need to adopt rules for the interaction of law enforcement agencies with victims of domestic violence and aggressors. For a detailed study of the research topic, the main directions for researching the concepts of victimization, the latency of domestic violence and prevention in this area were chosen. In order to avoid shortcomings in the recommendations for improving legislation on the prevention of domestic violence in the Republic of Kazakhstan during the study, these articles are based on the experience of foreign countries and doctrine. The scientific study has a number of results, which are as follows: systematization of the behavior of subjects of domestic violence for the further prevention of crimes in the field of domestic violence, as well as the importance of factors influencing the commission of unlawful acts in family and domestic relations. The creation of an effective mechanism for the prevention of domestic violence will reduce the level of offenses in this area, as well as increase the level of trust in law enforcement agencies in the area under study.